Finite Elements’ Simulation Of A Device Adapted To A Wheel Chair In Order To Automate It And 3d Modelling With MatLab - Ramírez Arias, José Luis; Martínez Quintero, Juan Carlos (Ingeniería Solidaria, 2011)
This article explains the methodology that the authors have used to create a device which allows automating a wheelchair for quadriplegic patients. It shows the analysis performed by the authors through finite elements regarding loading and efforts the device holds on. It shows the results of the model developed using the vrmllanguage in Matlab by means of the V-Realm Builder tool. It also shows the center of mass’ analysis due to the fact that it is a relevant criterion in the design, as the static stability of the chair depends upon it. Similarly, it details how the bolts support the motor and how the programming language used allowed charting the model.
Keywords: wheelchair; mathematical model; vrml